Correlation between anxiety in labor and duration as well as outcome - Rajabi, Fatemeh; Amir Ali Akbari, Sedigheh; Shams, Jamal; Alavi Majd, Hamid (Advances in Nursing & Midwifery, 2012)
Abstract Background and aim: Delivery is a stressful event. It seems that the cervix of an anxious woman does not dilate easily. The purpose of this study was determine the correlation between anxiety during labor and duration as well as outcome of delivery in women referring to hospitals affiliated to Shahid Behshti Medical University and Shahid Akbar Abadi Hospital . Materials and Methods: A descriptive correlational design was used. 200 women were selected via a multistage quota sampling in each hospital. A demographic and obstetrical questionnaire, Spielberg's State Trait Anxiety Inventory, and a checklist regarding the condition of the parturient women during hospitalization, duration of labor as well as delivery and Apgar score of the neonate were used for data collection.Data were analysed using SPSS 16 statistical software. Findings: Most women experienced moderate anxiety (%53/5).Mean of total time of delivery was 250/87±150/34 minutes, %94/5 was normal delivery and the mean of apgar score in first minute was 9 and in 5 minute was10. No significant correlation was found between anxiety in labor room and duration (first, second and third stage) as well as outcome (type and Apgar score) of delivery. Conclusion: Since most women experienced moderate anxiety, midwives and other healthcare workers should consider psychological aspects of mothers in labor rooms and make the atmosphere of these placed favorable addition, preparative educational courses during pregnancy is needed . Keywords: Anxiety, labor, delivery REFERENCES -Anderson L Poromaa IS Wulff M Astrom M Bixo M (2004). Implications of antenatal depression and anxiety for obstetric outcome. Obstetrics and Gynecology. 104 (3) 467-476. -Carson VB (2000). Mental Health Nursing. 2nd edition, Philadelphia: W.B. Saunders Company. -Chang MY Wang SY Chen C H (2002). Effects of massage on pain and anxiety during labour: A randomized controlled trial in Taiwan. Journal of Advanced Nursing. 38 (1) 68- 73. -Coad J Dunstal M (2001). Anatomy and Physiology for Midwives. Edinburgh, New York: Mosby. -Cunningham FG Williams JW (2010).Williams Obstetrics. 23 rd edition New York: Mc Graw- Hill Company. -Decherney HA Nathan L (2003) Current Obstetric & Gynecologic, 9th edition, New York, Mc Graw- Hill. -Gagnon A Waghorn K (1999).One to one nurse labor support of nuliparous women stimulated with oxytocin. Journal of Obstetric. Gynecologic&Neonatal Nursing. 28 (4) 371- 376. -Johnson RC SLADE P (2003). Obstetric complications and anxiety during pregnancy: is there a relationship? Journal of Psychosomatic Obstetrics and Gynecologic. 24 (1) 1-14 -Johnson C R Slade P (2002).Does fear of childbirth during pregnancy predicts emergency caesarean section. An International Journal of Obstetrics' and Gynecology. 109 (11) 1213- 1221. -Kaviany H Ahmady Abhary A etal (2002). Prevalance of anxiety disorder in Tehran city. Thinking and Behavior Journal.8 (31) 4-11 -Keogh E Hughes S Ellery D Daniel C Psy C Holdcroft A (2006). Psychosocial influences on women's experience of planned elective cesarean section. Psychomatic Medicine. 68 (1) 167-174. -Lang AJ Sorrell JT Rodgers CS Lebeck M (2006). Anxiety sensitivity as a predictor of labor pain. European Journal of Pain, 10 (3) 263-270. -Langer A Campero L Garcia C Reynoso S (1998). Effects of psychosocial support during labour and childbirth on breastfeeding, medical interventions, and mother's wellbing in a Mexican public hospital: a randomized clinical trial. British Journal of Obstetries and Gynaecology. 105 (10) 1056 – 1063 -Littleton HL Breikopf CR Berenson AB (2007). Correlates of anxiety symptoms during pregnancy and association with perinatal outcomes: A meta – analysis. American Journal of Obstetrics & Gynecology. 196 (5) 424- 432. -Motevally E Feizy Z Gangy T Haganny H (2003). [Does viewing of videotape effect on childbirth anxiety level of primigravida mothers?].Iran Journal of Nursing.16 (33) 100-104 (Persian). -Moslemabadi Farahani A Malekzadegan R Mohammadi F Hosseini (2005). [Effect of the one to one midwifery care during labor on modes of delivery Iran journal of nursing].18 (43) 71-82 (Persian). -Mallekpour Afshary F Salary P etal (2005). [Effect of childbiirth preparation of training on anxiety during pregnancy and parturition in primiparous women reffered to health centers in Mashhad city 2000] . Journal of Shaheed Sadoghy University of Medical Sciences. 13 (2) 39-44(Persian). -Nasiri Amiri F. Salmalian H, Hajiahmadi M (2009). [Association between Prenatal Anxiety and Spontaneous Preterm Birth]. Journal of Babol University of Medical Sciences.11 (4) 42-48. (Persian) -Nasiry,M.(2000).[Psychcological Health During Pregnancy and Parturition]. Tehran Boshra Publication.(Persian). -Mirzaei F,Keshtgar S Kaviani M etal (2009).The Effect of Lavender essence smelling during labor on cortisol and serotonin plasma levels and anxiety reduction in nulliparous woman. Journal of Kerman University of Medical Sciences.16 (3) 245-254 (Persian). -Masoomi R Lamiyan M Ghaedi S (2008). [Role of oxytocin in anxiety in the normal Parturition].Journal of Zahedan university of Medcial sciences. 10 (1) 53-58(Persian) -Pirdel M Pirdel L (2009). Perceived Environmental Stressors and Pain Perception During Labor Among Primiparous and Multiparous Women. Journal of Reproduction and Infertility. 10 (3) 224-217. -Sadock J Sadock VA Kaplan HI (2000).Comprehensive Textbook of Psychiatry. 7 th edition, Philadelphia: Lippincott Williams & Wilkins. -Shamaeian Razavi N Bahri Binabaj N Hoseiny Shahidy L PourHeidar M (2006). [The effect of maternal position on labor pain]. Journal of Ofogh-E-Danesh.12 (2) 16-21 (Persian) -Sadok B Sadok V (2005). [Abstract of Psychiatry] translated by .Pourafkary NVol (1,2).2 nd Edition .Tehran. Shahrab pub. (Persian) -Sedaghat S (1999). [Factors causing anxiety before and after delivery in primiparous women reffered to health centers and hospitals of Tehran and Shaheed Beheshty University of Medical Sciences in 1999]. Tesis for MS degree in Shaheed Beheshty University of Medical Sciences. (Persian) -Shamloo S (1994). [Mental Health].Tehran .Chehr pub. (Persian) -Wijma k (2003). Why focus" on fear of childbirth".Journal of Psychoso Obstetrics and Gyneocology. 24 (3)141-143. -World Health organization (2001). htt://www.emro.int/mnh/PublicInformation Part 6. htm.